Defending the Indefensible : the Global Asbestos Industry and its Fight for Survival. - McCulloch, Jock (OUP Oxford, 2008)
Until the mid-1960s, asbestos had a reputation as a lifesaver. In 1960, it became known that exposure to asbestos can cause mesothelioma, a virulent and lethal cancer. Yet the bulk of the world's asbestos was mined after 1960. This is the first global history of how the asbestos industry defended the product throughout the 20th century. - ;In the early twentieth century, asbestos had a reputation as a lifesaver. In 1960, however, it became known that even relatively brief exposure to asbestos can cause mesothelioma, a virulent and lethal cancer. Yet the bulk of the world's asbestos was mined a.